The Melted Coins - Dixon Franklin W.; Franklin W. Dixon (Canada Franklin W. Dixon, 1944)
Frank and Joe Hardy investigate a counterfeit ring stealing rare coins to melt down into face-value currency.
Keywords: the physical life cycle of currency and a Hardy Boys mystery novel; primarily revolves around themes of justice, friendship, and vigilance against fraud